Peran Pemilih Pemula Dalam Pengawasan Pemilu Partisipatif - Primadi, Agam; Efendi, David; Sahirin, Sahirin (Jurusan Ilmu Politik Universitas Bangka Belitung, 2019)
Law Number 7 year 2017 verse 101 mandated Badan pengawasan pemilu (Bawaslu:Bureau of election monitoring) as an institution monitoring electoral democracy proccess ranging from legislative, regional to president election. Considering its duty on electoral agenda, the need for BAWASLU’s innovation is one of the most significant factors to enhance the quality of general election. This paper is going to explain the inovation practice of BAWASLU in South Bangka in monitoring the general election and increasing the people participation. Descriptive anaysis is the method of this research by using primary data obtaining from particpatory activities of the researchers. Lastly, the paper concludes that the innovation is manifested through the existence of election-monitoring class by formulating the agent of participatory election monitoring in every district, and this method was effectively increased the political participation and consciousness of voters spesifically young voters.